Impact of the lanthanide size on the polymorphism and electrical properties of Ln5.4MoO11.1 (Ln = Nd, Sm and Gd) - Rubio-Vives, Rafael; Porras-Vázquez, José Manuel; Dos-Santos-Gómez, Lucía; Zamudio-García, Javier; Infantes-Molina, Antonia; Canales-Vázquez, J.; Marrero-López, David; Ramírez-Losilla, Enrique (Elsevier, 2023)
Mixed proton-electronic conductors are of great interest for high temperature electrochemical devices, such as hydrogen separation membranes. In this contribution, ceramics with composition Ln5.4MoO11.1 (Ln = Nd, Sm and Gd) were prepared by a freeze-drying precursor method. The resulting powders were sintered at 1500 ◦C and cooled down at different rates to investigate the different polymorphic forms: quenching (rapid cooling), 5 and 0.5 ◦C min-1. The ceramics were characterized by different techniques: X-ray diffraction, scanning and transmission electron microscopies and X-ray photoelectron and impedance spectroscopies. X-ray diffraction studies confirmed that all materials are single phase regardless of the cooling rate used. Those cooled by quenching present a simple cubic fluorite structure. At lower rates, 5 and 0.5 ◦C min-1, the cubic symmetry is stabilized as the size of the lanthanide decreases. However, electron diffraction studies indicated the formation of domains with superstructure ordering. Furthermore, XPS analysis showed the presence of mixed Mo6+ and Mo5+ for all compositions, which explains the electronic conduction in an oxidizing atmosphere. All materials are stable in reducing atmosphere and the ionic and electronic conductivities show opposite trends as the ionic radii of the lanthanide element becomes smaller, where the former decreases and the latter increases.
Keywords: Metales de las tierras raras; Hydrogen separation membrane; Lanthanide molybdate